2016
DOI: 10.1371/journal.pone.0161432
|View full text |Cite
|
Sign up to set email alerts
|

A Model for Dimerization of the SOX Group E Transcription Factor Family

Abstract: Group E members of the SOX transcription factor family include SOX8, SOX9, and SOX10. Preceding the high mobility group (HMG) domain in each of these proteins is a thirty-eight amino acid region that supports the formation of dimers on promoters containing tandemly inverted sites. The purpose of this study was to obtain new structural insights into how the dimerization region functions with the HMG domain. From a mutagenic scan of the dimerization region, the most essential amino acids of the dimerization regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
(56 reference statements)
0
5
0
Order By: Relevance
“…Despite the increasing knowledge regarding SOX8, it is still unclear about the contribution of SOX8 to mammalian cell development as well as the functional characterizations. The DNA‐dependent dimerization in sites that bear the (A/T)(A/T)CAA(A/T)G consensus sequence can be mainly ascribed to the SOX‐E family 35 . This study potently suggested that, SOX8 bound toGOLPH3 promoter, while regulating GOLPH3 transcription, translation and proliferation of TSCC cells.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Despite the increasing knowledge regarding SOX8, it is still unclear about the contribution of SOX8 to mammalian cell development as well as the functional characterizations. The DNA‐dependent dimerization in sites that bear the (A/T)(A/T)CAA(A/T)G consensus sequence can be mainly ascribed to the SOX‐E family 35 . This study potently suggested that, SOX8 bound toGOLPH3 promoter, while regulating GOLPH3 transcription, translation and proliferation of TSCC cells.…”
Section: Discussionmentioning
confidence: 69%
“…The DNA-dependent dimerization in sites that bear the (A/T)(A/T)CAA(A/T)G consensus sequence can be mainly ascribed to the SOX-E family. 35 This study potently suggested that, SOX8 bound toGOLPH3 promoter, while regulating GOLPH3 transcription, translation and proliferation of TSCC cells. Nonetheless, it is still unclear about whether SOX8 DNA-binding domain is involved in its binding with the GOLPH3 promoter.…”
Section: Discussionmentioning
confidence: 71%
“…The p.S30 ∗ and p.Cys71Hisfs ∗ 62 mutations do not contain the majority of the SOX10 protein including the HMG domain (DNA binding region) and predicted nuclear localization signals (NLSs). These mutants are therefore unlikely to form a homodimer or interact with other SOX10 proteins, given that the HMG domain has been reported to be important for dimer formation ( Ramsook et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…A bioinformatics survey of performed on a set of domains of unknown functions (DUFs) suggested that Orf63 may have nucleic acid binding properties 18 . Our observation that polar, solvent facing Orf63 on helix α2 affected activity, a sample of 15 N-Orf63 with a molar excess of a 32 bp palindromic dsDNA that was originally determined to be a high-affinity binding partner for the human Sox9 DNA binding domain 19 . A comparison of 1 H-15 N HSQC spectra of free and DNA-bound Orf63 showed no chemical shift changes or line broadening suggesting that in this limited context, Orf63 may require a specific DNA sequence to achieve high affinity binding or not bind dsDNA, at all.…”
Section: Resultsmentioning
confidence: 94%